Cultivar-specific responses of the citrus endophytic microbiome to Xanthomonas citri subsp. citri infection reveals Lysobacter as a key biocontrol taxon - Zhang, Yu; Ahmed, Waqar; Dai, Zhenlin; Meng, Han; Li, Hongmei; Moussa, Ihab M.; Ma, Yonglin; Zhang, Jinhao; Ji, Guanghai (Frontiers in Plant Science, 2025)
IntroductionCitrus canker, caused by Xanthomonas citri subsp. citri (Xcc), is a major threat to citrus production worldwide, resulting in significant losses in yield and fruit quality. This study investigates the differential responses of endophytic microbial communities to Xcc infection in citrus cultivars with distinct resistance levels, specifically comparing the highly susceptible Citrus reticulata cv. ‘Orah’ and the more resistant Fortunella crassifolia cv. ‘Cuimi’. Through high-throughput amplicon sequencing, we characterized the bacterial and fungal communities in both cultivars before and after Xcc inoculation.ResultsThe results revealed distinct shifts in microbial diversity, with bacterial community diversity largely maintained in resistant cultivars but significantly reduced in susceptible ones following Xcc infection. Conversely, fungal community richness decreased in both cultivars post-inoculation, with notable cultivar-specific changes in the relative abundance of key genera. Notably, Lysobacter emerged as the only bacterial genus that significantly increased in abundance in the resistant cultivar under pathogen pressure, highlighting its potential as a key biocontrol agent. Further, we identified several fungal genera, including Penicillium and Aspergillus, which proliferated in susceptible plants under pathogen pressure. The study also isolated and identified a Lysobacter antibioticus GJ-6 strain with potent antagonistic activity against Xcc, offering insights into its potential role in enhancing disease resistance.ConclusionsThis work provides a comprehensive understanding of how endophytic microbiomes differ between resistant and susceptible citrus cultivars, suggesting new avenues for developing sustainable biocontrol strategies to manage citrus canker. These findings underscore the potential of endophytes in mitigating plant diseases and advancing the application of microbiome-based interventions in agriculture.